Lewis acid catalyzed selective reactions of donor-acceptor cyclopropanes with 2-naphthols - Kaicharla, Trinadh; Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
Lewis acid-catalyzed reactions of 2-substituted cyclopropane 1,1-dicarboxylates with 2-naphthols is reported. The reaction exhibits tunable selectivity depending on the nature of Lewis acid employed and proceed as a dearomatization/rearomatization sequence. With Bi(OTf)(3) as the Lewis acid, a highly selective dehydrative [3+2] cyclopentannulation takes place leading to the formation of naphthalene-fused cyclopentanes. Interestingly, engaging Sc(OTf)(3) as the Lewis acid, a Friedel-Crafts-type addition of 2-naphthols to cyclo-propanes takes place, thus affording functionalized 2-naphthols. Both reactions furnished the target products in high regioselectivity and moderate to high yields.
Keywords: annulations; arenes; Lewis acids; reaction mechanisms; small ring systems